CENTRAL BANK DIGITAL CURRENCIES IN THE INDONESIAN SETTING: QUESTIONS & CHOICES - David K Linnan (Journal of Central Banking Law and Institutions, 2023)
Central Bank Digital Currencies or CBDC have attracted increasing attention worldwide. Discussions take place chiefly at the institutional central bank level, and among financial and monetary economists, but now are moving into legal and political spaces. Meanwhile, Bank Indonesia or BI, the Indonesian central bank, has been an active proponent of a digital Rupiah for several years, seemingly focused on payment system improvements, problematic to the extent on-going digitalisation of the economy is not purely a payment system exercise.The Indonesian Parliament or DPR recently authorised in Law No. 4/2023 BI’s creation and management of a digital Rupiah, but open issues remain: (1) the DPR’s emphasis in its guidelines for the digital Rupiah contemplates currently only a domestic rather than crossborder digital Rupiah; (2) the DPR seemingly contemplated broader financial inclusion and more equitable development as a practical matter, while BI’s prior proposals seemed more focused on efficiency and banking sector; and (3) domestic CBDC’s introduction probably constitutes a dress rehearsal for an eventual international CBDC, so a planning function lies hidden. Digital Rupiah’s implementation presumably lies 12 to 24 months ahead, taking place under a new Indonesian President to be elected in 2024, implying new senior financial sector regulators as well. The best legal approach would be for BI to manage the digital Rupiah through external clearing and settlement institutions, and there are numerous international economic law complications in the hidden planning exercise if domestic is to become international digital Rupiah over time. Developing versus developed country CBDC concerns are simply different.